Platycodin D and voluntary running synergistically ameliorate memory deficits in 5 × FAD mice via mediating neuromodulation and neuroinflammation - Liu, Junxin; Jiang, Jiahui; He, Chuantong; Zhou, Longjian; Zhang, Yi; Zhao, Shuai; Yang, Zhiyou (Frontiers in Aging Neuroscience, 2024)
Introduction Alzheimer’s disease (AD) is the leading cause of dementia, and currently, no effective treatments are available to reverse or halt its progression in clinical practice. Although a plethora of studies have highlighted the benefits of physical exercise in combating AD, elder individuals often have limited exercise capacity. Therefore, mild physical exercise and nutritional interventions represent potential strategies for preventing and mitigating neurodegenerative diseases. Our research, along with other studies, have demonstrated that platycodin D (PD) or its metabolite, platycodigenin, derived from the medicinal plant Platycodon grandiflorus, exerts neuroprotective effects against amyloid β (Aβ)-induced neuroinflammation. However, the combined effects of PD and physical exercise on alleviating AD have yet to be explored. The current study aimed to investigate whether combined therapy could synergistically ameliorate memory deficits and AD pathology in 5 × FAD mice. Methods Five-month-old 5 × FAD mice were randomly assigned to four groups, and received either PD (5 mg/kg/day, p.o.), voluntary running, or a combination of both for 47 days. Nest building test, locomotion test, and Morris water maze test were used to evaluate the cognitive function. Immunohistochemical and ELISA analysis was performed to determine Aβ build-up, microglia and astrocytes hyperactivation, and survival neurons in the hippocampus and perirhinal cortex. Real-time quantitative PCR analysis was used to assess the polarization of microglia and astrocytes. HPLC analysis was performed to measure monoamine neurotransmitters in the hippocampus. Results and discussion The combination of PD and voluntary running synergistically restored nest-building behavior, alleviated recognition and spatial memory deficits, and showed superior effects compared to monotherapy. In addition, the PD and voluntary running combination reduced Aβ build-up, decreased hyperactivation of microglia and astrocytes in the hippocampus and perirhinal cortex, promoted the polarization of inflammatory M1 microglia and reactive astrocytes toward beneficial phenotypes, and lowered systemic circulating pro-inflammatory cytokines while increasing anti-inflammatory cytokines in 5 × FAD mice. Furthermore, combined therapy effectively protected neurons and increased levels of 5-hydroxytryptamine (5-HT) and dopamine (DA) in the hippocampus of 5 × FAD mice. In conclusion, the combination of PD and voluntary running holds great potential as a treatment for AD, offering promise for delaying onset or progression of AD.